Comparison of Analgesic Outcomes of Bilateral Transversus Abdominis Plane Block with Intravenous Tramadol Following Cesarean Delivery Under Spinal Anesthesia - Muhammad Aatir Fayyaz, Asif Mehmood, Hina Bashir, Ranna Musarrat, Muhammad Ramzan Shah, Syed Aftab Haider, (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To compare the effect of bilateral transversus abdominis plane (TAP) block analgesia and intravenous tramadol in post-operative period following cesarean delivery under spinal anesthesia. Patients and Methods: In this randomized controlled trial we included 100 patients who underwent elective cesarean delivery from 1-June-2021 to 01-January-2022 in Nishtar Hospital Multan. All patients were given spinal anaesthesia using standard technique. In group A, patients were given TAP block at the end of the procedure. Group B, was given spinal anaesthesia alone with intravenous tramadol 50 mg and analgesia requirement were noticed at 12 hours postoperatively. Results: Mean age was 28.28±4.61 years. Mean BMI was 23.60±2.33 kg/m2. Mean gestational age of patients was 39.96±1.26 weeks. Mean duration of procedure was 48.10±5.39 minutes. Mean duration in TAP block was 48.53±5.30 minutes and in IV analgesia group was 47.67±5.50 minutes (p-value 0.42). Mean VAS for pain was 4.27±1.50. Mean VAS for pain in TAP block was 3.46±0.93 and in IV analgesia group was 5.07±1.56 with p-value of <0.001. The mean VAS score after 24 hours was 0.7±0.5 in TAP group versus 3.1±0.7 in IV analgesia only (p-value <0.0001). Time of first rescue analgesia was 212±60 minutes in TAP group versus 77±23 minutes in IV analgesia only group (p-value <0.001) [Table 1]. Conclusion: The use of the bilateral TAP block in patients undergoing elective cesarean delivery can reduce postoperative pain and analgesic usage for up to 24 hours after the procedure.